The holiday practices of seniors and their implications for social tourism: A Wallonian perspective. (November 2020) - Diekmann, Anya; Vincent, Martin; Bauthier, Isabelle
Abstract: With an ageing population and the increasing prevalence of age-related constraints, social tourism providers and policy-makers face significant challenges in providing holidays for seniors. Based on a large database from a research project in Wallonia (Belgium) implemented from 2015 till 2018, the study identifies the different types of holiday arrangements and activities associated with the benefits of holidays, largely in terms of wellbeing. It then examines whether they are age-related or not, and if so how, and how they can inform social tourism policies that target seniors. Data from the sample of 4144 respondents show a variety of age-related significant associations, with thresholds at retirement and after the age of 70. The study examines these associations in the context of various social theories of ageing and sets out the implications for social tourism policy-makers and providers. Highlights: Seniors' holiday practices and their implications for social tourism policies Identification of senior holiday arrangements and activities associated with the benefits of holidays Certain holiday arrangements and activities with thresholds at retirement and after the age of 70 Confirmation of associations between well-being, retirement, and holidays Empirical large-scale data about under-researched senior tourists contributing to developing social tourism policies